Species Diversity With Comprehensive Annotations of Wood-Inhabiting Poroid and Corticioid Fungi in Uzbekistan - Gafforov, Yusufjon; Ordynets, Alexander; Langer, Ewald; Yarasheva, Manzura; de Mello Gugliotta, Adriana; Schigel, Dmitry; Pecoraro, Lorenzo; Zhou, Yu; Cai, Lei; Zhou, Li-Wei (Frontiers in Microbiology, 2020)
Uzbekistan, locating in Central Asia, harbours high diversity of woody plants. Diversity of wood-inhabiting fungi in the country, however, remained poorly known. In this study, the knowledge of wood-inhabiting poroid and corticioid fungi (Agaricomycetes, Basidiomycota) in Uzbekistan accumulated from 1950 to 2020 was summarized on the basis of 790 fungal occurrence records: 185 from recently collected specimens, 101 from herbarium specimens made by earlier collectors, and 504 from literature-based records. All data were deposited as a species occurrence record dataset in the Global Biodiversity Information Facility (GBIF) and also summarized in the form of an annotated checklist in this paper. All 286 available specimens were morphologically examined. Of them, 138 specimens, from which 114 ITS and 85 LSU nrDNA sequences were newly generated, were also phylogenetically analyzed. In total, we confirm the presence of 153 species of wood-inhabiting poroid and corticioid fungi in Uzbekistan, of which 31 species are reported for the first time in Uzbekistan, including 19 also new to Central Asia. These 153 fungal species inhabit 100 host species from 42 genera of 23 families. Polyporales and Hymenochaetales are the most recorded fungal orders, and are most widely distributed around the study area. This study for the first time comprehensively updated and annotated the checklist of wood-inhabiting poroid and corticioid fungi in Uzbekistan. Such study should be expanded to other countries to further clarify species diversity of wood-inhabiting fungi around Central Asia